2016
DOI: 10.1523/jneurosci.2197-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Cdk5 Regulation of the GRAB-Mediated Rab8-Rab11 Cascade in Axon Outgrowth

Abstract: Neurons communicate with each other through their axons and dendrites. However, a full characterization of the molecular mechanisms involved in axon and dendrite formation is still incomplete. Neurite outgrowth requires the supply of membrane components for surface expansion. Two membrane sources for axon outgrowth are suggested: Golgi secretary vesicles and endocytic recycling endosomes. In non-neuronal cells, trafficking of secretary vesicles from Golgi is regulated by Rab8, a member of Rab small GTPases, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 78 publications
0
30
0
Order By: Relevance
“…Moreover, during axon outgrowth, Cdk5 was shown to regulate Rab proteins, which coordinate vesicle trafficking, fusion, and maturation. (42) During recent years, endocytosis has emerged as a central process in cancer. Endocytic circuitries are deeply interconnected with the activation and execution of various pathways that regulate cancer growth, progression, and metastasis, including small GTPases, integrin, epithelial-mesenchymal transition, and growth factor receptor signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, during axon outgrowth, Cdk5 was shown to regulate Rab proteins, which coordinate vesicle trafficking, fusion, and maturation. (42) During recent years, endocytosis has emerged as a central process in cancer. Endocytic circuitries are deeply interconnected with the activation and execution of various pathways that regulate cancer growth, progression, and metastasis, including small GTPases, integrin, epithelial-mesenchymal transition, and growth factor receptor signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Although Rab11A has been implicated in the maturation of REs [31], we hypothesize that Rab22A possibly functions downstream of Rab11 or Rab11-tubular structures morphed into a different set of REs. In the latter case, we predict that Rab11 possibly interacts with either GRAB-Rab8A [32] or Rabin8-Rab8A [33,34] proteins that were observed during the neurite outgrowth of PC12 cells. We favour the earlier model, since the overexpression of Rab11A could not rescue the KIF13A-positive tubules either in Rab22A-or BLOC-1-knockdown cells (Fig EV1G).…”
mentioning
confidence: 89%
“…It has been reported that GRAB (a guanine nucleotide exchange factor for Rab8a) mediates the Rab11a-Rab8a cascade mechanism and facilitates axonal growth (Furusawa et al, 2017). Therefore, we tested the effect of GRAB on TNT formation.…”
Section: Grab Regulates Tnt Formation Independently Of Rab8amentioning
confidence: 99%
“…The mouse catecholaminergic neuronal CAD cell line (mouse catecholaminergic neuronal cell line, Cath.aDifferentiated) (Gousset et al, 2013) was grown in Gibco OptiMEM supplemented with 10% fetal bovine serum (FBS) and 1% penicillin-streptomycin. pEGFP-C1-Rab plasmids library, pEGFP-C1-Rab8a(Q67L), pEGFP-C1-Rab8a(T22N), pEGFP-C1-Rab11a(Q70L), pEGFP-C1-Rab11a(S25N) and pEGFP-C1-Rabin8, and pEGFP-C1-GRAB were prepared as described previously (Furusawa et al, 2017;Ishida et al, 2012;Matsui and Fukuda, 2011;Tsuboi and Fukuda, 2006). GFP-VAMP3 was a kind gift from Thierry Galli (Center of Psychiatry and Neuroscience, INSERM U894, Paris France).…”
Section: Cell Lines Plasmids and Transfection Proceduresmentioning
confidence: 99%